2009
DOI: 10.1577/t08-178.1
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide Assessment of Mercury Dynamics in North Carolina Water Bodies and Fish

Abstract: Mercury contamination of aquatic systems has received much attention recently because of potential health effects on humans and wildlife. Although the factors affecting mercury deposition, its conversion to biologically active methylmercury, and its bioaccumulation in aquatic systems have been identified, equivocal results for particular species and systems have hampered policy making. Our study addresses this problem through a comprehensive, statewide synthesis of the available data on fish mercury contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 57 publications
5
43
2
Order By: Relevance
“…The p values from the test of simple main effects are reported in Supplemental Data, Table S2. with MeHg concentrations in biota [15,16,[40][41][42][43]. The hypothesized mechanism for the observed positive relationship between MeHg concentration and productivity is the stimulation of MeHg production by microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p values from the test of simple main effects are reported in Supplemental Data, Table S2. with MeHg concentrations in biota [15,16,[40][41][42][43]. The hypothesized mechanism for the observed positive relationship between MeHg concentration and productivity is the stimulation of MeHg production by microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…The bottom-up effects of nutrients potentially influence the flux of MeHg from aquatic systems by regulating productivity and emergent insect biomass [10][11][12]. Nutrients may also alter the flux of MeHg by affecting the concentrations of MeHg of insects as has been shown for other consumers [13][14][15][16]. The top-down influence of predation by fish could affect MeHg flux by reducing the biomass and altering the taxonomic composition of larval and emergent insects [11,12,[17][18][19].…”
Section: Introductionmentioning
confidence: 97%
“…Bluegill exist at the intermediate trophic level, foraging on a mix of zooplankton, plant material, and benthic invertebrates (Werner and Hall 1988). Power analyses based on a previous dataset (Sackett et al 2009) suggested that collections of five individuals of a restricted size range per species (i.e., 10 fish per system) would be sufficient to confidently quantify differences in fish tissue Hg among lakes. Largemouth bass collections were limited to individuals that were 300-400 mm total length (TL) and bluegill collections were limited to 150-200 mm TL.…”
Section: Selection Of Sampling Sitesmentioning
confidence: 99%
“…Ravichandran 2004), geographic region (e.g. Sackett et al 2009), and chlorophyll a (e.g. Lange et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some investigators support the idea that the commonly positive relationship between fish size and Hg concentration is frequently due to exposure time and to increased Hg in prey for larger fish rather than to variations in growth (Trudel and Rasmussen 2006). In addition, Hg accumulation and distribution patterns depend on the species, specific tissue, and environmental degree of contamination (Maury-Brachet et al 2006;Sackett et al 2009). However, D. labrax and L. aurata, which have different biological and ecological traits (e.g., metabolism, reproduction, activity levels, lipid content), demonstrated similar patterns of Hg distribution in their tissues (both T-Hg and O-Hg).…”
Section: Discussionmentioning
confidence: 97%